Pengaruh Return On Assets, Net Profit Margin, Current Ratio, Rasio Kas Operasi, Debt To Asset Ratio terhadap Devident Payout Rasio (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2019 - Herlina Anasia Nadeak; Desy Mariani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of return on assets, net profit margin, current ratio, operating cash ratio, debt to asset ratio on dividend payout ratio in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period of 95 companies. The data used in this study were obtained from financial statement data and annual reports. The population in this study are food and beverage sector companies listed on the Indonesian Stock Exchange. The sampling technique used was the purposive sampling method and obtained 250 sample data from 50 companies. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 20. The results of this study indicate that net profit has a positive and significant effect on cash dividends, operating cash flow and debt policy have a negative and significant effect on cash dividends. While profitability and liquidity have no effect on cash dividends.